The Influence of the MURDER Learning Strategy on Understanding of IPAS in Grade V of SD AL-Azhar 1 Bandar Lampung - Nada Naurah Putri Azizah; Yuberti; Hasan Sastra Negara (Journal of Learning Improvement and Lesson Study, 2025)
The low understanding of science concepts among elementary school students remains a problem influenced by teacher-centered learning. This condition requires the implementation of learning strategies that can activate students' cognitive processes systematically. This study aims to analyze the effect of the MURDER learning strategy assisted by Wordwall media on the understanding of science concepts in fifth grade students. The study used a quantitative approach with a quasi experimental design of the pretest–posttest control group type. The research sample consisted of 52 students divided into an experimental class and a control class. Data were collected through a concept understanding test and analyzed using an independent t-test. The results showed a significant increase in concept understanding in the experimental class compared to the control class. This finding confirms that a structured cognitive learning strategy supported by interactive media is effective in significantly improving the understanding of science concepts.